Heat Treatment and Analysis of Al- 7005 Alloys Reinforced with Sic Metal Composite - A, Arun.; V.Sathiyamoorthy, Dr; P, Amirthalingam.; A, Manikandan; K, Manikandan; R, Narendran (International Journal of Engineering and Technology, 2018)
This paper deals with the 7005 aluminium alloy characterization which has similar physical properties to 6061 aluminium alloy, depending on the temper, may be slightly stronger. To increase their mechanical and physical properties silicon carbide had been introduced in it as reinforcement. Based on mass three different compositional were made and mixed thoroughly, and cast. Stir casting method is used for casting proportioned alloys. Heat treatment process is carried out after casting the alloy is mixed in the three proper compositions. Mechanical properties like hardness, Tensile strength and impact strength were conducted and analyzed. Properties can be altered in a better way using silicon carbide as an reinforcement in aluminium-7005.Â Â